Molecular Evolution of Human Norovirus GII.2 Clusters - Li, Xingguang; Liu, Haizhou; Rife Magalis, Brittany; Kosakovsky Pond, Sergei L.; Volz, Erik M. (Frontiers in Microbiology, 2021)
Background: The human norovirus GII.2 outbreak during the 2016–2017 winter season was of unprecedented scale and geographic distribution. Methods: We analyzed 519 complete VP1 gene sequences of the human norovirus GII.2 genotype sampled during the 2016-2017 winter season, as well as prior (dating back to 1976) from 9 countries. Phylodynamic analyses of these sequences were performed using maximum likelihood and Bayesian statistical frameworks in order to estimate viral evolutionary and population dynamics associated with the outbreak. Results: Our results revealed an increase in the genetic diversity of human norovirus GII.2 during the recent Asian outbreak and diversification was characterized by at least eight distinct clusters. Bayesian estimation of viral population dynamics revealed a highly fluctuating effective population size, increasing in frequency during the past fifteen years. Conclusions: Despite an increasing viral diversity, we found no convincing evidence of an elevated evolutionary rate or significant selection pressure during, or leading to, the recent outbreak, indicating viral evolutionary adaptation was not responsible for the volatility of or spread of the virus during this time.